TRISODIUM PHOSPHATE 2% EFFECT ON SETTING TIME ALGINAT MATERIALS - Zwista Yulia Dewi; Ira Artilia; Silvia Padilah; Muhammad Farras (Fakultas Kedokteran Gigi Unjani, 2022)
Alginate is widely used in dentistry as an impression material. Manipulation of commercial alginate impression materials with the addition of Trisodium Phosphate (TSP). It is known to prolong the setting time of alginate by reacting it first with calcium sulfate. Dental students in their first grade sometimes have difficulty manipulating alginate so they need a longer manipulation time. There is no alginate product with a longer setting time in the market. From this study, we added 2% TSP to add setting time for dental education. The purpose of this study to characterize was to determine the compressive strength of alginate molding materials that have been added with TSP to commercial alginate products with factory standards. Setting time, compressive strength, EDS, and SEM was used as a characterization. This research was true experimental research. It was conducted using normal type printed materials with one of the brands available in the market. The results of this study were then analyzed using paired T-test, the compressive strength of alginate without and without TSP 2% was a significant difference. The addition of 2% TSP affected the compressive strength of the alginate impression material. DOI : 10.54052/jhds.v2n1.p111-122